HOMOGENEOUS IDEALS AND JACOBSON RADICAL - Najaryan, N.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
In this paper the Jacobson radical of an algebraFX/ H is studied, where FhXi is a free associative algebra of countable rank over infinite field F and H is a homogeneous ideal of the algebrFX. The following theorem is proved: the Jacobson radical of an algebra FX/ H is a nil ideal.